Public Speaking Skills Needs of English Majors at Universiti Sains Malaysia (LSP International Journal, 2018)
Demands of the academic disciplines as well as the versatility and competitiveness in today's job market have prompted scholars, educators and researchers to emphasise the importance of learners’ success in handling oral communication skills, in general, and public speaking skills, in particular (Payne and Carlin 1994; Yamashiro and Johnson, 1997; Lucas, 2007). In line with this necessity, the current investigation draws into the public speaking skills needs of the English majors at Universiti Sains Malaysia (USM). The study aims to identify the forms and skills of public speaking frequently used by the students. It also explores the students’ lacks and communication apprehension in public speaking. Thirty-nine second, third and fourth year students majoring in English at the School of Humanities, USM participated in the study. The results indicate that besides the frequent use of a number of preparation and delivery skills by the English majors, certain types of speech, such as small group, informative and persuasive appeared to be among the communicative tasks the students confront in their academic discourse discipline. The findings also reveal that the majority of the respondents are competent enough in performing almost all the public speaking skills, although they do experience moderate level of communication apprehension. Some implications for the learners, lecturers and course developers are stated briefly.